Decision management in transoral robotic surgery: Indications, individual patient selection, and role in the multidisciplinary treatment for head and neck cancer from a European perspective. (15th June 2015) - Lörincz, Balazs B.; Jowett, Nathan; Knecht, Rainald
Abstract: Background: Transoral robotic surgery (TORS) has become an accepted first‐line treatment for T1 and T2 head and neck squamous cell carcinoma (HNSCC). The growing popularity of this procedure is the result of mounting skepticism as to the survival and quality of life (QOL) benefits of primary chemoradiation over definitive surgery, the rising incidence of human papillomavirus (HPV)‐positive oropharyngeal squamous cell carcinoma (OPSCC) in progressively younger patients, and the advantages of TORS over transoral laser microsurgery (TOLM) and open surgery. Methods: The authors use their experience and data gained from the TORS‐based management of >100 patients to establish a systematic approach to the use of TORS in HNSCC. Results: This approach is constructed on a framework which goal is to select the primary treatment option that is most likely to reduce morbidity while preserving function and maintaining oncologic safety. Conclusion: A consensus regarding the indications of TORS and its role in the multidisciplinary management of HNSCC is to be established. © 2015 Wiley Periodicals, Inc. Head Neck 38 : E2190–E2196, 2016